Molecular genetic characterization of two solvent pathway dehydrogenases from Clostridium Acetobutylicum - Youngleson, Jonathan Sinclair (Department of Molecular and Cell Biology, 2017)
Clostridium acetobutylicum P262 is an endospore-forming Gram-positive anaerobic bacterium, which has been used for the industrial production of acetone and butanol from carbohydrate substrates. This study forms part of a wider research effort into the genetics and molecular biology of C. acetobutylicum, which has as an ultimate goal the commercial improvement, and a fundamental understanding of the ABE fermentation. The aim of this study was to isolate and characterize genes involved in solventogenesis. The cloning, expression and characterization of the terminal solventogenic butanol dehydrogenase gene ( adhl), and the central pathway β-hydroxybutyryl-CoA dehydrogenase gene (hbd), which form part of a but operon are described.